Genomic variants in mouse model induced by azoxymethane and dextran sodium sulfate improperly mimic human colorectal cancer - Qingfei Pan (Nature Portfolio, 2017)
Abstract Mouse model induced by azoxymethane (AOM) and dextran sodium sulfate (DSS) is generally accepted as an ideal object to study on the carcinogenesis mechanisms of human colorectal cancer (CRC). The genomic responses to the AOM/DSS treatment in mouse that possibly lead to elucidation of CRC pathological mechanism are still poorly understood. For the first time, we investigated the cancer genome landscape of AOM/DSS mouse model by exome sequencing, to testify its molecular faithfulness to human CRC. Of 14 neoplastic samples, 7575 somatic variants were identified, which resulted in 2507 mutant genes and exhibited a large diversity in both colorectal aberrant crypt foci (ACF) and tumors even those tissues that were gained from the similar morphology or same treatment period. Cross-species comparison of the somatic variants demonstrated the totally different patterns of variable sites, mutant genes and perturbed pathways between mouse and human CRC. We therefore come to a conclusion that the tumorigenesis at genomic level in AOM/DSS model may not be properly comparable with that in human CRC, and the molecular mechanism elicited from this animal model should be carefully evaluated.